Large bored piles proceedings of the symposium organized by the Institution of Civil Engineers and the Reinforced Concrete Association at the Institution of Civil Engineers, London, February 1966. (Institution of Civil Engineers, 1966)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a symposium organized with the Reinforced Concrete Association held in February 1966.